Carbamide Peroxide Determination in Tooth Whitening Using a Reagentless HRP-Biosensor - Vidal, Isabelle Goncalves; Tescarollo Dias, Iara Lucia; de Oliveira Neto, Graciliano; de Vasconcellos Lanza, Marcos Roberto; Taboada Sotomayor, Maria Del Pilar [UNESP] (Taylor & Francis Inc, 2009)
A rapid and effective method for carbamide peroxide (CP) quantification in pharmaceuticals is proposed. The reagentless biosensor was prepared by using lyophilized turnip extract as horseradish peroxidase (HRP) enzyme source. The biosensor presented the best performance. The measurements were carried out in 0.1mol L-1 Pipes buffer (pH 6.0). At-100mV vs. Ag|AgCl, a linear response range from 3.0 to 25.0mmol L-1 was obtained. The quantification and detection limits were 1.2 and 0.4mmol L-1, respectively, and the response time was 0.5s. The biosensor repeatability, storage, and lifetime were excellent, allowing a satisfactory CP quantification in real pharmaceutical samples, when compared with those obtained by the official method.
Keywords: Amperometric biosensor; brassica napus L; carbamide peroxide; HRP; lyophilization procedure